2020
DOI: 10.3389/fonc.2020.00602
|View full text |Cite|
|
Sign up to set email alerts
|

A Non-invasive Method to Diagnose Lung Adenocarcinoma

Abstract: Purpose: To find out the CT radiomics features of differentiating lung adenocarcinoma from another lung cancer histological type.Methods: This was a historical cohort study, three independent lung cancer cohorts included. One cohort was used to evaluate the stability of radiomics features, one cohort was used to feature selection, and the last was used to construct and evaluate classification models. The research is divided into four steps: region of interest segmentation, feature extraction, feature selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Besides, our study proved that GLDM_ low gray level emphasis was an important indicator for distinguishing MIAs from IACs in subsolid nodules; studies also proved that low gray level emphasis helps to differentiate lung adenocarcinoma from another lung cancer histological type (21) and predict NSCLC survival (22).…”
Section: Discussionsupporting
confidence: 55%
“…Besides, our study proved that GLDM_ low gray level emphasis was an important indicator for distinguishing MIAs from IACs in subsolid nodules; studies also proved that low gray level emphasis helps to differentiate lung adenocarcinoma from another lung cancer histological type (21) and predict NSCLC survival (22).…”
Section: Discussionsupporting
confidence: 55%
“…Radiomic features (such as intensity, shape, texture, or wavelet), extracted from medical images, when combined with clinical parameters can make clinical decision more precise [ 11 ]. It has shown a great ability to be the biomarkers in predicting clinical events of lung cancer patients, recent examples like predicting the response of enzymes, gene and immunity therapy which are associated with lung tumor [ 12 ], evaluating the drug reaction [ 13 ], radiation pneumonitis [ 14 ], and distinguishing lung cancer histologic subtypes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both are important factors for predicting the response of rectal cancer to nCRT [26] , [27] , and have significant correlation with clinical prognostic factors [28] . Some studies reported that the three radiomics features showed good repeatability [26] , [29] . In our study, the three radiomics features could predict PFS or OS in patients with stage III-IV CRC.…”
Section: Discussionmentioning
confidence: 99%